2017
DOI: 10.1111/ijfs.13489
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assess of high hydrostatic pressure and superfine grinding on physicochemical and antioxidant properties of grape pomace

Abstract: Summary In this study, we evaluate the effects of high hydrostatic pressure (HHP) and superfine grinding (SFG) treatment on grape pomace. The results showed that the HHP treatment improved physicochemical and antioxidant properties of grape pomace than the SFG treatment did. Moreover, the results of SEM indicated that the HHP‐treated grape pomace turned to have more lamellar structure, resulting in more hydrophilic groups exposed to improve WRC, WSC and SDF content. The results of FT‐IR spectra indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 48 publications
(51 reference statements)
7
27
1
1
Order By: Relevance
“…Therefore, the HHP treatment had better effect in improving the functionality of grape pomace than that of the superfine grinding treatment. These results showed partly differences with those of Seeram, Aviram, and Zhang (), Sheng et al (), and Abountiolas and Nunes (). These differences can be probably due to kind of fruit, maturity, composition, growing and climatic factors, and harvest time.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Therefore, the HHP treatment had better effect in improving the functionality of grape pomace than that of the superfine grinding treatment. These results showed partly differences with those of Seeram, Aviram, and Zhang (), Sheng et al (), and Abountiolas and Nunes (). These differences can be probably due to kind of fruit, maturity, composition, growing and climatic factors, and harvest time.…”
Section: Resultscontrasting
confidence: 57%
“…Polyphenol content of juices from Rubus fruit, orange, apples, and grapes also positively correlate with AOC while AA has a minimal contribution (Deighton, Brennan, Finn, & Davies, ; Wand, Cao, & Prior, ). Sheng et al () reported a comparative assess of high hydrostatic pressure and superfine grinding on physicochemical and antioxidant properties of grape pomace. Sheng et al () determined 63.33 mg GAE/g, 38.12, and 85.61 total phenol in control, superfine grinding (SFG), and high hydrostatic pressure (HHP) grape pomace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheng et al . () reported that HPP treatment at 200 MPa could improve the content of bioactive components, such as proanthocyanidins, anthocyanin and soluble dietary fibre (SDF) as well as enhancing the antioxidant properties of grape pomace. Moreover, Hokmollahi & Ehsani () have summarised the advantages of applying HPP in cheese manufacturing.…”
Section: Nonthermal Processing Technologiesmentioning
confidence: 99%
“…The WHC and OHC of the cellulose powder samples were determined using the method described by Sheng et al () and Nsor‐Atindana, Zhong, and Mothibe () with slight modifications. To determine WHC, ultrapure water (8 ml) was transferred into centrifuge tubes containing sample (0.20 g) at room temperature for 24 hr and centrifuged at 4,000 rpm for 10 min, and then the supernatant was removed.…”
Section: Methodsmentioning
confidence: 99%